Pengaruh kualitas pelayanan, kualitas produk dan harga Terhadap kepuasan pelanggan air minum isi ulang “Biru” di Villa Mutiara Gading Bekasi - Listyowati, Dwi; Nanda, M. Rifky Ika; Saragih, Rudi Hedianton; Marpaung, Oktavia; Siagian, Frisca L. (Journal of Information System, Applied, Management, Accounting and Research, 2025)
Water is a basic human need that is used for drinking, cleaning and others. The water consumed must be clean water free from germs and bacteria. To fulfill the need for drinking water, there are now many mineral water businesses or bottled water produced by factories. In addition to bottled water there is also a refill water business. The source of bottled water and refill water is mountain water. But the water cleaning process is different. Bottled water is filtered at the factory, while refillable water is filtered on-site. Customers will choose to use bottled water, or refill water. Consumers who choose refill water must pay attention to the quality of the product, whether this refill water is safe for consumption, whether the filtering is correct. Refill water is chosen because the price is relatively cheaper than the price of bottled water. In addition, refill water filling services are also considered by customers. Good service, for example, no need to queue, customers are helped to carry gallons, becomes a satisfaction for its customers. “Biru” refill water has a clear product and contains ozone, with a price that is relatively cheaper than bottled water, and the service at the refill depot is very good. One of the “Biru” refill water depots is in Villa Mutiara Gading Bekasi. This depot is the best depot for the Western region. This study aims to determine the effect of service quality, product quality, price on customer satisfaction of refill water “Biru” at Villa Mutiara Gading Bekasi, either partially or simultaneously. By taking a sample of 88 “Biru” refill water customers at Villa Mutiara Gading Bekasi, the results showed that either partially or simultaneously, service quality, product quality, price have a significant effect on customer satisfaction of “Biru” refill water at Villa Mutiara Gading Bekasi.